2019
DOI: 10.7196/sajch.2019.v13i3.1640
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Healthy Active Kids South Africa 2018 Report Card

Abstract: Physical activity (PA) is beneficial for the physical and mental health of children and adolescents (0-17 years old), [1,2] while higher levels of sedentary behaviour (particularly screen time) are associated with unfavourable health outcomes. [3,4] Nutrition has been recognised as a factor contributing to the development of overweight/obesity in children and adolescents. [5] A nutrient-dense diet and regular PA are beneficial for overall child growth, health and wellbeing. [6] Healthy lifestyle behaviours als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…These ECD stakeholders and government representatives were seen as a vital part of the process, and would be able to provide insight into the acceptability and feasibility of disseminating these guidelines, given that movement behaviours are not currently a priority issue in early childhood in SA. Other academic researchers with expertise in movement behaviours in the early years or with expertise in early childhood development were identified from the Scientific Advisory Group of the Healthy Active Kids South Africa Report Card 13 and invited to be part of the consensus panel. All those invited were given an outline of the guideline development process and informed of the consensus panel meeting that was to take place in April 2018.…”
Section: Form Consensus Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…These ECD stakeholders and government representatives were seen as a vital part of the process, and would be able to provide insight into the acceptability and feasibility of disseminating these guidelines, given that movement behaviours are not currently a priority issue in early childhood in SA. Other academic researchers with expertise in movement behaviours in the early years or with expertise in early childhood development were identified from the Scientific Advisory Group of the Healthy Active Kids South Africa Report Card 13 and invited to be part of the consensus panel. All those invited were given an outline of the guideline development process and informed of the consensus panel meeting that was to take place in April 2018.…”
Section: Form Consensus Panelmentioning
confidence: 99%
“…Overall, there was a paucity of literature describing the physical activity, sedentary behaviour and sleep of 0-5 year old children in SA. 8 This was highlighted in the Healthy Active Kids South Africa 2018 Report Card 13 There were a number of recent studies on movement behaviours in this age group, and while these studies were done with relatively small, localised samples, they represent the best available evidence. However, the generalisability of these findings to all SA children is limited.…”
Section: Narrative Review Of South African Literaturementioning
confidence: 99%
“…Although the benefits of PA have been well identified, physical inactivity remains a major public health problem [ 13 , 14 ]. The Healthy Active Kids South Africa (HAKSA) 2018 report indicated that 50% of children are not meeting the recommended average of 60 min of MVPA per day [ 15 ]. It appears that the adoption of urban lifestyles, introduction of technology-related devices and the shift from active transport, particularly in children from rural areas, are all responsible for decreasing levels of PA [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining preschoolers' movement behaviours and gross motor skills in Soweto highlighted that many young children were short sleepers and seemed to be going to bed late (7) . Concerns around South African children's diets include the lack of dietary diversity in young children's diets, as many are consuming a diet that is high in starchy foods and low in fruits and vegetables, and the consumption of sugar-sweetened beverages, salt and fast food (21,22) . It is important to understand the contexts in which these behaviours occur, as it is recognised that factors like socio-economic circumstances and elements of the built environment have a bearing on childhood obesity and related behaviours (23,24) .…”
mentioning
confidence: 99%